Genetics and Regulation of Nitrogen Fixation in Free-Living Bacteria - Klipp, Werner.; Klipp, Werner.; Masepohl, Bernd.; Masepohl, Bernd.; Gallon, John R.; Gallon, John R.; Newton, William E.; Newton, William E. (Nitrogen Fixation: Origins, Applications, and Research Progress ;, 2005)
Genetics and Regulation of Nitrogen-Fixing Bacteria This book is the second volume of a seven-volume series, which covers all fields of research related to nitrogen fixation - from basic studies through applied aspects to environmental impacts. Volume II provides a comprehensive and detailed source of information concerning the genetics and regulation of biological nitrogen fixation in free-living prokaryotes. This preface attempts to provide the reader with some insight into how this volume originated, how it was planned, and then how it developed over the several years of its production. Once the editorial team was established, the first job was to decide which of the many free-living diazotrophs that have been subjected to genetic analysis should be included in this volume. Would we need to develop specific criteria for selection or would the organisms, in effect, select themselves? Of course, Klebsiella pneumoniae and Azotobacter vinelandii, which have served (and still serve) as the main model organisms for the genetic analysis of diazotrophy, plus some of the other bacteria described in this volume, did indeed select themselves. However, there was considerable discussion surrounding well-characterized fixing species, like Azorhizobium caulinodans and Herbaspirillum seropedicae, both of which are able to fix atmospheric N under free-living conditions.